Analysis of the Form of Moral Message Delivery in the Film "Ipar Adalah Maut" by Hanung Bramantyo: Analysis of the Form of Moral Message Delivery in the Film "Ipar Adalah Maut" by Hanung Bramantyo - Nada Ana Salsabila; Irwan Satria; Dina Putri Juni Astuti (International Journal of Technology and Education Research, 2026)
This research is motivated by the importance of literary works of film as a medium of mass communication, namely communication through mass media. Film act as a means to convey values or moral messages to society. The main problem in this research is how these moral messages can be constructed and conveyed through various cinematic and narrative elements such as plot, dialogue, characterization, symbolism and cinematography. Often the moral message in the film is not conveyed directly, but through a series of events or conflicts experienced by the characters. This study aims to analyze the form of conveying moral message in the film Ipar Adalah Maut by Hanung Bramantyo. This study uses a qualitative approach with a descriptive research type. Data were collected through observation documentation, recordings and notes through the film Ipar Adalah Maut by Hanung Bramantyo. The results of the study show that film Ipar Adalah Maut conveys moral messages through two main forms, namely explicitly through character dialogue and narration, and implicitly through visual symbols conflict and storyline. The forms of moral messages found include the values of honesty, loyalty, responsibility, and the consequences of betrayal in family relationships. The conclusion of this study is that the film Ipar Adalah Maut is an effective film in conveying moral messages through various forms of delivery.